Novel Nanotherapeutics for Cancer Immunotherapy by PD-L1-Aptamer-Functionalized and Fexofenadine-Loaded Albumin Nanoparticles - Xialian Lai; Fengjiao Yao; Yacong An; Xundou Li; Xian-Da Yang (Molecules, 2023)
Immune checkpoint blockade (ICB) is an important strategy for cancer treatment and has achieved remarkable clinical results. Further enhancement of the efficacy of ICB therapy with a new technical approach is of potential medical importance. In this study, we constructed a novel nanotherapeutic agent (PDL1-NP-FEXO) for cancer immunotherapy by attaching PD-L1 aptamers to albumin nanoparticles that were loaded with H1-antihitamine fexofenadine (FEXO). FEXO has been reported to enhance the immunotherapy response by reducing the immunosuppressive M2-like macrophages in the tumor microenvironment. The albumin nanoparticle was fabricated using a self-assembly method. A dynamic light scattering (DLS) study revealed that the average size of PD-L1 aptamer-modified nanoparticle without FEXO (PDL1-NP) was 135.5 nm, while that of PDL1-NP-FEXO was 154.6 nm. Similar to free PD-L1 aptamer, PDL1-NP could also bind with PD-L1-expressing tumor cells (MDA-MB-231). Of note, compared with free PD-L1 aptamer, PDL1-NP significantly boosted tumor inhibition in CT26-bearing mice. Moreover, PDL1-NP-FEXO further enhanced the antitumor efficacy vs. PDL1-NP in an animal model, without raising systemic toxicity. These results indicate that PDL1-NP-FEXO represents a promising strategy to improve ICB efficacy and may have application potential in cancer immunotherapy.